2014
DOI: 10.1186/1471-2377-14-19
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with fear of falling in people with Parkinson’s disease

Abstract: BackgroundThis study aimed to comprehensibly investigate potential contributing factors to fear of falling (FOF) among people with idiopathic Parkinson’s disease (PD).MethodsThe study included 104 people with PD. Mean (SD) age and PD-duration were 68 (9.4) and 5 (4.2) years, respectively, and the participants’ PD-symptoms were relatively mild. FOF (the dependent variable) was investigated with the Swedish version of the Falls Efficacy Scale, i.e. FES(S). The first multiple linear regression model replicated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
90
4
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(119 citation statements)
references
References 42 publications
19
90
4
6
Order By: Relevance
“…The importance of walking difficulties corroborates previous studies that targeted contributing factors to fall-related self-efficacy in people with PD [10,12]; walking difficulties alone explained then 60-68% of the variation in scores. Another PD study that targeted balance confidence [21] also identified walking difficulties to be of importance.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The importance of walking difficulties corroborates previous studies that targeted contributing factors to fall-related self-efficacy in people with PD [10,12]; walking difficulties alone explained then 60-68% of the variation in scores. Another PD study that targeted balance confidence [21] also identified walking difficulties to be of importance.…”
Section: Discussionsupporting
confidence: 75%
“…Several PD studies have investigated associated factors to FOF by using multivariate regression analyses [10,12,[19][20][21]. However, two of these studies were based on data collected by means of postal surveys and therefore lacked clinical data [12,19] and three studies included few (n = 4-6) potential independent variables [19][20][21], resulting in non-comprehensive analyses of contributors to FOF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As to the anteroposterior displacement, the cognitive variables included explained 23% of the variability of the anteroposterior displacement, increasing to 34% when the individual and clinical variables were added. A recent study (Lindholm et al 2014) has shown that cognitive impairments, particularly EFs, are closely related to motor symptoms, especially with postural instability. Hence, the results of the correlations found showed that at least one cognitive test was correlated with balance.…”
Section: Somatosensory and Motor Researchmentioning
confidence: 99%
“…Recent studies have shown that impairments in EFs are closely related to motor symptoms, particularly with postural instability (Lindholm et al 2014). This may be due to the important role of these functions in anticipation, planning, and coordination (McCloskey and Perkins 2012).…”
Section: Introductionmentioning
confidence: 99%